Production of Radioactive 22Na in Core-collapse Supernovae: The Ne-E(L) Component in Presolar Grains and Its Possible Consequences on Supernova Observations - Marco Pignatari; Sachiko Amari; Peter Hoppe; C. Fryer; S. Jones; A. Psaltis; A. M. Laird; F. Herwig; L. Roberti; Thomas Siegert; Maria Lugaro (The Astrophysical Journal)
Presolar graphite grains carry the isotopic signatures of their parent stars. A significant fraction of presolar graphites show isotopic abundance anomalies relative to solar for elements such as O, Si, Mg, and Ca, which are compatible with nucleosynthesis in core-collapse supernovae (CCSNe). Therefore, they must have condensed from CCSN ejecta before the formation of the Sun. Their most puzzling abundance signature is the ^22 Ne-enriched component Ne-E(L), interpreted as the effect of the radioactive decay of ^22 Na ( T _1/2 = 2.6 yr). Previous works have shown that if H is ingested into the He shell and not fully destroyed before the explosion, the CCSN shock in the He-shell material produces large amounts of ^22 Na. Here we focus on such CCSN models, showing a radioactive ^26 Al production compatible with grain measurements, and analyze the conditions of ^22 Na nucleosynthesis. In these models, ^22 Na is mostly made in the He shell, with a total ejected mass varying between 2.6 × 10 ^−3 M _⊙ and 1.9 × 10 ^−6 M _⊙ . We show that such ^22 Na may already impact the CCSN light curve 500 days after the explosion, and at later stages it can be the main source powering the CCSN light curve for up to a few years before ^44 Ti decay becomes dominant. Based on the CCSN yields above, the 1274.53 keV γ -ray flux due to ^22 Na decay could be observable for years after the first CCSN light is detected, depending on the distance. This makes CCSNe possible sites to detect a ^22 Na γ -ray signature consistently with the Ne-E(L) component found in presolar graphites. Finally, we discuss the potential contribution from ^22 Na decay to the Galactic positron annihilation rate.